Fostering Ethical, Legal, and Social Implications Research in Tribal Communities: The Center for the Ethics of Indigenous Genomic Research. (October 2020) - Hiratsuka, Vanessa Y.; Beans, Julie A.; Reedy, Justin; Yracheta, Joseph M.; Peercy, Michael T.; Saunkeah, Bobby; Woodbury, R. Brian; O'Leary, Marcia; Spicer, Paul G.
Genomic research raises unique ethical concerns among Alaska Native and American Indian (AN/AI) people and their communities. The Center for the Ethics of Indigenous Genomic Research (CEIGR) was created to foster research that takes these concerns into account while considering the sovereign status of AN/AI tribal nations. Relationships developed within CEIGR have allowed for effective, collaborative research among individuals who come from diverse cultures, political and historical backgrounds, and academic disciplines, and who work for organizations with varying resources, capacities, and expectations. The CEIGR framework may inform other groups seeking to conduct social science research related to genomic research with tribal people and their communities.